Pengaruh Nilai Pelanggan Dan Kualitas Pelayanan Terhadap Kepuasan Dampaknya Terhadap Loyalitas Nasabah - Mokoagouw, Steve E.A. (JURNAL RISET BISNIS DAN MANAJEMEN, 2018)
The purpose of this study is to analyze the influence of customer value on customer satisfaction BNI KCU Manado, the influence of service quality to customer satisfaction BNI KCU Manado, the influence of customer value to customer loyalty through customer satisfaction BNI KCU Manado, the influence of service quality on customer loyalty through customer satisfaction of BNI KCU Manado and the influence of customer satisfaction to customer loyalty BNI KCU Manado. This type of research is a kind of research associative by using data analysis technique that is path analysis (Path Analysis). The result of the research shows that (1) Customer Value has significant effect on Customer Satisfaction of BNI KCU Manado, (2) Service Quality has no significant effect on Customer Satisfaction of BNI KCU Manado, (3) Customer value has no significant effect on Customer Loyalty through Customer Satisfaction of BNI KCU Manado (4) Service Quality has no significant effect on Customer Loyalty through Customer Satisfaction of BNI KCU Manado, and (5) Customer Satisfaction has significant effect on Customer Loyalty of BNI KCU Manado.Keywords: Customer Value, Service Quality, Satisfaction, LoyaltyÂ